The Changes in Ideology in the Adaptation of Riordan’s The Lightning Thief - Dita Dwi Yulianti; Ikwan Setiawan; Dina Dyah Kusumayanti (SUAR BETANG, 2023)
This research aims to find some ideologies in the adaptation of a novel into a film that uses qualitative research methods and comparative methods. These ideologies lead us to find out the motive beyond the adaptation work. So, this research discusses two objects. The first object is how the transformations of The Lightning Thief adaptation (from novel to film) are. The second object is the motive beyond the adaptation of The Lightning Thief from a book into a film. This research uses Linda Hutchon’s theory of adaptation as a basis of theory, Roland Barthes’ Mythologies, and the theory film of mise-en-scene as the method to find out the ideology from both the novel and film. The results show some transformations of the ideologies from the book into a film. The novel brings the emergence of feminism, the motherhood role, collectivism, fantasy as the uniqueness of the story, and cultural universality. While the film changes into the emergence of patriarchal ideology, the fatherhood role, individualism, competitiveness, and freedom of American values. These results show three motives of adaptation: cultural capital, personal motive, and economic lures. AbstrakPenelitian ini bertujuan menemukan beberapa ideologi dalam adaptasi novel ke dalam film dengan menggunakan metode penelitian kualitatif dan metode komparatif. Ideologi ini membawa kita untuk menemukan motif dalam karya adaptasi. Jadi, penelitian ini membahas dua objek. Objek pertama adalah bagaimana transformasi adaptasi The Lightning Thief (dari novel ke film). Objek kedua adalah apa motif dibalik adaptasi The Lightning Thief dari sebuah novel menjadi sebuah film. Penelitian ini menggunakan teori adaptasi Linda Hutchon sebagai dasar teori,Mythologies Roland Barthes dan teori film mise-en-scene sebagai metode untuk menemukan ideologi baik dari novel maupun film. Hasilnya menunjukkan beberapa transformasi ideologi dari novel ke film. Novel membawa kemunculan feminisme, peran keibuan, kolektivisme, fantasi sebagai keunikan cerita, dan universalitas budaya. Sementara film berubah menjadi kemunculan ideologi patriarki, peran kebapakan, individualisme, daya saing, dan kebebasan sebagai nilai-nilai Amerika. Hasil ini menunjukkan tiga motif adaptasi, yaitu modal budaya, motif personal, dan iming-iming ekonomi.